Encouraging Registered Reports at the Canadian Journal of Experimental Psychology (CJEP): An Invited Tutorial by Oshiro et al. (2024) - Titone, Debra; Dyson, Ben; Fernandes, Myra; Joanisse, Marc (American Psychological Association, 2024)
Continuing Canadian Journal of Experimental Psychology’s ongoing commitment to Open Science, we invited Oshiro et al. (2024) to submit a peer-reviewed tutorial of the typical format and to offer key pieces of advice when preparing Registered Reports.
©American Psychological Association, 2024. This paper is not the copy of record and may not exactly replicate the authoritative document published in the APA journal. Please do not copy or cite without author's permission. The final article is available, upon publication, at: https://doi.org/10.1037/cep0000361
Keywords: Open Science; registered reports; publishing; research practices